Effect of Work Stress and Leader-Member Exchange on Adaptive Performance through Innovative Work Behavior of Generation Z Employees in East Java - Ni Nyoman Asti Stya Putri; Shinta Setia (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effect of work stress and leader–member exchange on adaptive performance through the mediating role of innovative work behavior among Generation Z employees, in line with increasing demands for adaptation in a dynamic work environment. Methodology: This study used a quantitative approach through an online questionnaire survey of Generation Z employees in East Java who met the research criteria, resulting in 145 valid responses. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and structural model. Results: The results showed that work stress had a significant negative effect on innovative work behavior and adaptive performance, while leader–member exchange had a significant positive effect on both variables. Innovative work behavior was also found to play a significant mediating role in explaining employee adaptability. Findings: Innovative work behavior emerged as a key behavioral mechanism that translates work stress conditions and leadership relationship quality into individual adaptability. Novelty and Originality: This study provides new empirical evidence on the dynamics of Generation Z employee adaptation by placing innovative work behavior as the main psychological channel connecting work demands and leadership resources with adaptive performance, thereby enriching the understanding of behavioral mechanisms in the context of the young workforce. Conclusion: This study concludes that adaptive performance among Generation Z is not directly shaped by work pressure or leadership, but is significantly guided by individual innovation capacity, affirming the central role of innovative work behavior as the primary mechanism for developing workforce adaptability. Type of Paper: Empirical research article.